Theatrical scenic art - Troubridge, Emma (The Crowood Press, 2018)
This is a detailed guide to the creative process of painting and preparing scenery for theatre. The book offers key insights into the role of the scenic artist, detailing the process from planning, budgeting and developing samples through to creating and delivering the final finishes.